Effects of specially designed training on functional abilities and blood markers of oxidative stress in elite judo athletes - Radovanovic, D.; Bratic, M.; Nurkic, M.; Kafentarakis, I.; Kolias, C. (World Congress of Performance Analysis of Sport VIII, 2008)
Strenuous exercise is characterized by an increased oxygen consumption and disturbance of intracellular prooxidant-antioxidant homeostasis. Under physiological conditions, these deleterious species are mostly removed by the cellular antioxidant systems, which include antioxidant vitamins, protein and non-protein thiols, and antioxidant enzymes. Some conditions associated with intense exercise, such as local tissue hypoxia or elevated tissue temperatures, could also contribute to reactive oxygen production. Evidence that muscle conditioning results in upregulation of antioxidant defenses also suggests a close relationship between reactive oxygen and contractile activity. Therefore, there appears to be a significant role for reactive oxygen in normal muscle physiology. However, a number of conditions may lead to an imbalance of oxidant production and antioxidant defense, and these, presumably, do create conditions of oxidant stress. To defend against ROS, muscle cells contain complex cellular defence mechanisms to reduce the risk of oxidative injury. Two major classes (enzymic and non-enzymic) of endogenous protective mechanisms work together to reduce the harmful effects of oxidants in the cell. The mechanisms of exercise-induced oxidative stress are not well understood. There is no evidence that this affects sporting performance in the short term, although it may have longer term, not necessarily detrimental, health consequences. The results obtained suggest that specially designed judo training can significantly increase anaerobic power in elite judo athletes, but also affect oxidative stress biomarkers. Significant increase of erythrocyte MDA and plasma CAT can be consider as negative effects of this training program. While certain biomarkers of oxidative stress was increased following functionally effective specially designed judo training, future research may investigated methods of reducing macromolecule oxidation, possibly through the use of antioxidant supplementation.